Withering Lily: Human Struggle to Face the Negative Effects of Social Media - Chrissya Margaretha (Institute of Research and Community Outreach - Petra Christian University, 2021)
This creative thesis focuses on understanding the relation between using social media and social anxiety. The goal of this work is to understand what causes the disorder to appear after exposures to social media and the effect it has on someone. To reach that goal, this creative thesis uses the Presentation of Self Theory and Social Anxiety theory to understand how social media could cause social anxiety and how it affects their life externally . It shows that the problem comes from the desire to become “perfect” in society and after that it would lead to the heightened fear of judgement that is the trigger of social anxiety. Further, social anxiety would prevent someone from living a good social life. Therefore, by understanding people’s desire to be “perfect” and the effects of social anxiety, we can see that being overly afraid of being judged on social media could ruin someone’s life.Keywords: Social Media, Social Anxiety, Presentation of Self, Screenplay, Cyberpunk